Factors affecting growth and toxin production of microcystis aeruginosa towards better water quality management in the Philippines and Cambodia - HUL Seingheng
Cyanobacteria can survive abd grow in various types of aquatic habitat ranging from freshwater, brackish, and sea water. Cyanobacteria bloom is becoming an annoying problem in most countries in the world. Toxigenic Microcystis aeruginosa is a common blooming species of cyanobacteria in most water bodies. Knowing the factors and conditions for their growth, survival and bloom is important in the management and control of water bodies that are prone to their bloom and toxin contamination. For its management, water quality was monitored for a year in Tonle Sap lake of Cambodia. Turbidity, nitrate and phosphate levels in the lake were higher during the summer period April to May 2009. In May 2009, microcystins were found in Kompong Luong site and in an offshore site but the gene of toxic microcystis was found only in Kompong Luong site.